Research Trends in Chemical Literacy: A Systematic Literature Review from 2013 to 2022 - Pardiana Pardiana (Scientia Publica Media, 2024)
As early as 1989, the term chemical literacy was introduced. Chemical literacy refers to an individual’s understanding of particle matter, reactions, laws, theories, and chemical applications in life. Research on chemical literacy has been conducted by several researchers in several countries. However, it is rare to find research that focuses on the trend of chemical literacy research with the use of systematic analysis of literature review. This study aims to analyze research on chemical literacy and look at its trends to find further research opportunities. The analysis was carried out with systematic literature review with the main material from the scopus database. Scopus is one of the most comprehensive databases of peer-reviewed journals. The literature search was conducted online in September 2022 with 1 keyword, namely chemical literacy. A total of 23 articles related to chemical literacy in the 2013-2022 span were analyzed and mapped. Based on the results of the analysis, it is known that the trend of chemical literacy research takes place fluctuatingly. Of the 9 countries in the Scopus database that research the topic of chemical literacy, Indonesia is the country with the most contributors to articles that discuss this research topic on chemical literacy.